CRYPTO INVESTMENT CYBERCRIME - Rahmad Tantawi; Muhammad Salman; Tuti Meutia; Safrizal (Jurnal Penelitian Ekonomi Akuntansi, 2024)
This bibliometric analysis examines studies related to crypto investment cybercrime. This research is a literature review using the Harzing Publish or Perish and Mendeley search tools, limited to studies related to crypto investment cybercrime in the 2017-2023 research period and published in Scopus-indexed journals. The results of the study show that only four publications were found to be directly related to crypto investment cybercrime, so it is recommended that further research be conducted empirically and published in Scopus-indexed journals. The limitations of this study are that the review was only conducted through a literature review with a research period of the last five years, and it is recommended that future researchers analyze “crypto investment cybercrime” empirically and then conduct research on the financial sector analysis unit, such as in the banking sector and other financial institutions.